Photocatalytic decomposition of an ago dye using transition-metal-doped tungsten and molybdenum carbides - Mabuea, Busiswe Petunia; Swart, Hendrik Christoffel; Erasmus, Elizabeth (American Chemical Society, 2022)
The preparation, characterization, and photocatalytic application of tungsten or molybdenum carbides (Ni-WC, 1, Co-WC, 2, Ni-MoC, 3, Co-MoC, 4, NiCo-WC, 5, NiCo-MoC, 6, NiFe-WC, 7, and NiFe-MoC, 8) doped with transition metals (Fe, Co, and Ni) are reported. These transition-metal carbide (TMC) particles show that the submicrometer globular particles agglomerated to form larger particles, with smaller crystallites present on the surface of the large particles. These crystallite sizes range between 4 and 34 nm (as calculated from X-ray diffraction data) depending on the metal dopant and type of carbide. Oxidation of the metal carbides is evident from the two sets of photoelectron lines present in the X-ray photoelectron spectroscopy (XPS) of the W 4f area. The Mo 3d spectra reveal four sets of photoelectron lines associated with oxidized MoO2 and MoO3 as well as Mo2+ and Mo3+ associated with MoC1–x. The XPS of the dopant metals Ni, Co, and Fe also show partial oxidation. The photocatalytic decomposition of Congo red (an azo dye) is used as a model reaction to determine the photocatalytic activities of the transition-metal carbides, which is related to the TMCs’ optical band gap energies.
Keywords: Ago dye; Transition-metal-doped tungsten; Photocatalytic decomposition; Molybdenum carbides